Effect of single resistance genes and their pyramid on the diversity of Xanthomonas oryzae pv. oryzae population under field conditions as revealed by insertion sequence-polymerase chain reaction (Is-PCR) : - Nguyen, Dac Khoa (University of the Philippines Los Banos, 2005)
The specific obectives are to group xoo isolates of contemporary populations collected from rice fields in the Philippines based on their DNA fingerprints generated from IS-PCR using J3 primer; To assess the genetic variation of Xoo populations between years, experimental sites, and among rice lines; To make inference on the effect of single resistance genes and their pyramid on the population structure of Xoo under field conditions which can be used as a guide in the deployment of resistance.